Tata Kelola Ekstrakurikuler Olahraga dalam Internalisasi Nilai Disiplin di MTs Nurul Ali Secang - Abdul Ghofur; Ahmad Fuad Hasyim Hafid Suyuthi (MUADDIB: Jurnal Pendidikan Agama Islam, 2026)
This research was conducted at MTs Nurul Ali Secang Magelang, where sports extracurricular activities serve as a vital medium for fostering student discipline, yet their effectiveness remains contingent upon the quality of management implemented. This study aims to analyze the management of sports extracurricular activities in shaping students' disciplined character through the management functions of planning, organizing, actuating, and controlling. Employing a qualitative approach with a descriptive case study design, data were gathered through participant observation, in-depth interviews, and documentation. Purposive sampling was utilized to select key informants, including the madrasah principal, sports extracurricular supervisors, teachers, and student participants. The research results indicate that the planning phase is grounded in the madrasah's strategic work program, aligned with student needs, and oriented toward character development. Organization is executed through a clear division of tasks and responsibilities among the madrasah administration, supervisors, and relevant stakeholders. Implementation is conducted routinely and scheduled systematically, emphasizing time discipline, adherence to regulations, and individual responsibility. Furthermore, supervision is performed through consistent attendance monitoring, behavioral observation, and periodic activity evaluations. Overall, the management of sports extracurriculars contributes positively to shaping students' disciplined character, as evidenced by their improved punctuality, consistent participation, adherence to school rules, and personal accountability.